Предмет: Алгебра,
автор: oxanapavlova
4^(x+ корень из(x^(2)-2)) -5*2^(x-1+ корень из(x^(2) -2)) =6
Ответы
Автор ответа:
0
[a-b] означает корень из a-b
a) [2x-4]-[x-5]=1
2x-4+x-5-1=2[(2x-4)(x-5)]
9x^2-60x+100=4(3x^2-14x+20)
-3x^2-4x+20=0
d=16+240=256
x1=(4-16)/6=-2 - не подходит, т.к. (2х-4)=-8<0
x2=(4+16)/6=10/3
b) 2x^2+[2x^2-4x+1]=4x+8
2x^2-4x-8+[2x^2-4x+1]=0
Обозначим 2x^2-4x+1=t, получим
[t]=9-t
t=81-18t+t^2
решив его, выполни проверку
a) [2x-4]-[x-5]=1
2x-4+x-5-1=2[(2x-4)(x-5)]
9x^2-60x+100=4(3x^2-14x+20)
-3x^2-4x+20=0
d=16+240=256
x1=(4-16)/6=-2 - не подходит, т.к. (2х-4)=-8<0
x2=(4+16)/6=10/3
b) 2x^2+[2x^2-4x+1]=4x+8
2x^2-4x-8+[2x^2-4x+1]=0
Обозначим 2x^2-4x+1=t, получим
[t]=9-t
t=81-18t+t^2
решив его, выполни проверку
Похожие вопросы
Предмет: Алгебра,
автор: lzprshmtt
Предмет: Французский язык,
автор: demyantop1
Предмет: Геометрия,
автор: svetikk9576
Предмет: Математика,
автор: 1527574534238746
Предмет: Алгебра,
автор: dimarhyme